Falling against incivility spirals or standing to maintain individuality: a social conformity perspective - Ali, Syed Ahmad; Azeem, Muhammad Umer; Yazdani, Naveed; Bajwa, Sami Ullah; Aslam, Haris (Emerald Publishing, 2025)
Purpose The main purpose of this paper is to empirically investigate the spiraling effects of workplace incivility. In doing so, the authors examine how workplace incivility begets other forms of mistreatment such as ostracism and abusive supervision, which in turn hinders employees’ job performance. In addition, the authors also test the buffering role of social skills in this process. Design/methodology/approach This study investigates a mediated moderation model with multitime and multisource data from 205 employees working in different Pakistani-based organizations (self-rated at T1 and supervisor rated at T2). Findings The results of this study provide support to the predictions that workplace incivility diminishes employees’ ability to perform through parallel mediations of ostracism and abusive supervision. The empirical findings also show that social skills moderate the negative relationship between abusive supervision and job performance. Originality/value This work extends the contemporary slant in workplace incivility, ostracism and abusive supervision literature by providing empirical evidence of spiraling effects of workplace incivility. In addition, the authors also tested the critical buffering role of social skills in mitigating the negative effects of such mistreatments at work